A case study of source-sink relationships using shoot girdling and berry classification (Vitis vinifera L. cv. Cabernet Sauvignon) - Joubert, Chandre (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScAgric)--Stellenbosch University, 2013.